Lipid profiles of vegetarian and non-vegetarian children at risk of overweight or obesity - Arie Purwana; IKG Suandi; Endy Paryanto Prawirohartono (Indonesian Pediatric Society, 2010)
Background The type, amount, and composition of a diet may affect the levels of cholesterol in blood. Itis believed that children adhering to a vegetarian diet have lower total cholesterol levels and lower body mass indexes compared to children with non-vegetarian (omnivorous) diets. We wish to compare cholesterol levels of vegetarian and non-vegetarian Indonesian children who are at risk of overweight or obesity.Objective To compare lipid profiles of vegetarian and no-vegetarian children who are at risk for overweight or obesity.Methods We performed a cross-sectional study in January and February 2010. Subjects for this study came from Denpasar, Bali. Subjects filled questionnaires as well as underwent history-taking, anthropometric measurements, and blood testing. We performed lipid profile analyses on their blood samples. We used the independent t test and Mann-Whitney test for statistical analysis of the data. The level of significance was set at P <0.05.Results Our study included forty-four children at risk for overweight or obesity with a vegetarian or non-vegetarian diet. We found that vegetarian children had lower mean total cholesterol (144 mg/dL) than that of non-vegetarian children (171 mg/dL), a statistically significant difference of P=0.014. In addition, vegetarian children had lower mean triglyceride levels (150 mg/dL) than those of nonô€€¶vegetarian children (264 mg/dL), a statistically significant difference of P =0 .025.Conclusion Among Balinese children at risk of overweight or obesity, vegetarians have significantly lower mean total cholesterol and triglyceride levels than non-vegetarians.